Contribution of Ulama' Melayu in Islamic education - Said, Mohamed Mohamed Tolba (ALNIL ENTERPRISE (002095879-P), 2019)
This book is based on the collection of researches conducted by the researchers of Islamic Education, Kulliyyah (Faculty) of Education, International Islamic University Malaysia (IIUM). This Book serve as a guide and reference for the Muslims community to enhance their knowledge and understanding the role of (ulama'Melayu) in the development of Islamic education in the range of 16th century to 20th century. Basically, this book consists of I I chapters about the Malay scholars, their biographies, their contributions in Islamic education and , its significance towards the (Muslim Ummah)